(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
BOOK REVIEW: Violence against women. Realities, challenges and actors in the implementation of the National Law 26485 in La Pampa by Daniela M. J. Zaikoski Biscay and BetsabéPolicastro (compilers) 2 EdUNLPam, 2017